Chitosan conduits filled with simvastatin/Pluronic F‐127 hydrogel promote peripheral nerve regeneration in rats. Issue 2 (3rd April 2017) - Guo, Qi; Liu, Can; Hai, Bao; Ma, Teng; Zhang, Wen; Tan, Jie; Fu, Xin; Wang, Hong; Xu, Yingsheng; Song, Chunli
Abstract: Treating peripheral nerve defects represents a clinical challenge, and nerve conduits lacking an internal scaffold lead to limited large nerve gap regeneration. Here, we bridged 10‐mm sciatic nerve defects in rats with a chitosan conduit filled with 0, 0.5, or 1.0 mg of simvastatin in Pluronic F‐127 hydrogel. We assessed subsequent nerve regeneration using the sciatic functional index (SFI), electrophysiological assessments, Fluoro‐Gold (FG) retrograde tracing, gastrocnemius muscle mass measurements, and histological and immunohistochemical assessments of nerve regeneration. Ten weeks after implantation, the chitosan conduit filled with simvastatin/Pluronic F‐127 hydrogel promoted nerve regeneration; there were significant increases in the SFI, compound muscle action potential peak amplitude, motor nerve conduction velocity, FG‐labeled neuron number in the dorsal root ganglia, myelin sheath thickness, axon diameter, gastrocnemius wet weight, and muscle fiber area percentage in the gastrocnemius muscle (all p < 0.05). The expression levels of neurotrophic factors, such as pleiotrophin, hepatocyte growth factor, vascular endothelial growth factor, and glial cell line‐derived neurotrophic factor, were also found to be increased. The results suggest that chitosan conduits filled with simvastatin/Pluronic F‐127 hydrogel improved peripheral nerve regeneration and functional recovery in rats, which may have been related to the increased expression of several endogenous neurotrophic factors. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 787–799, 2018.